Injury epidemiology in a national football team of the Middle East - Eirale, C.; Hamilton, B.; Bisciotti, G.; Grantham, J.; Chalabi, H. (Scandinavian Journal of Medicine & Science in Sports, 2012)
Many football epidemiological studies have been performed but only two of them have investigated injury risk in a national football team. In the present study, the senior male Qatar national football team was followed prospectively for two seasons. All injuries that were incurred during training and matches were recorded, together with match and training exposure time. Principal findings were (i) a higher injury incidence during matches than during training, (65.9 vs 4.3/1000 h, P<0.001), (ii) a high incidence of muscular strain during matches (23.2/1000 h) and (iii) a greater severity of injury in games than in regular training or camp situations (19.5 vs 8.4 vs 6.7 days, P<0.05). Despite the unique environmental, social and cultural setting in the Middle East, these findings are consistent with previous data from European football, suggesting that international guidelines on injury prevention and management may be applied in this region.